Perceptions of lecturers and students regarding discriminatory experiences and sexual harassment in academic medicine – results from a faculty-wide quantitative study - Sabine Ludwig; Sabine Jenner; Ralph Berger; Sylvie Tappert; Christine Kurmeyer; Sabine Oertelt-Prigione; Mandy Petzold (BMC Medical Education, 2024)
Abstract Background Discrimination and sexual harassment are prevalent in higher education institutions and can affect students, faculty members and employees. Herein the aim was to assess the extent of discriminatory experiences and sexual harassment of students and lecturers at one of the largest teaching hospitals in Europe. We analyze whether there are differences between lecturers and students, different study programs as well as sex/gender differences. Methods In an interdisciplinary, iterative process, a semi-standardized questionnaire was developed and sent to N = 7095 students (S) of all study programs and N = 2528 lecturers (L) at Charité—Universitätsmedizin Berlin, Germany. The study was conducted from November 2018 to February 2019. Besides a broad range of questions on sociodemographic background allowing for diversity sensitive data analysis, they were asked if they had witnessed and/or experienced any form of discrimination or sexual harassment at the medical faculty, if yes, how often, the perceived reasons, situational factors and perpetrators. Results The response rate was 14% (n = 964) for students and 11% (n = 275) for lecturers. A proportion of 49.6% of students (L: 31%) reported that they have witnessed and/or experienced discriminatory behavior. Sexual harassment was witnessed and/or experienced by 23.6% of students (L: 19.2%). Lecturers (85.9%) were identified as the main source of discriminatory behavior by students. Directors/supervisors (47.4%) were stated as the main source of discriminatory behavior by lecturers. As the most frequent perceived reason for discriminatory experiences sex/gender (S: 71%; L: 60.3%) was reported. Women and dental students experienced more discriminatory behavior and sexual harassment. Conclusions Discriminatory behavior is experienced by a significant number of students and lecturers, with power structures having a relevant impact. Dental students and women appear to be particularly exposed. Specific institutional measures, such as training programs for lecturers and students are necessary to raise awareness and provide resources. Furthermore, national preventive strategies should be thoroughly implemented to fight discrimination and harassment at the workplace.